2013
DOI: 10.3168/jds.2012-6492
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: In vitro antimicrobial susceptibility of Mycoplasma agalactiae strains isolated from dairy goats

Abstract: This study examined the susceptibility to several antimicrobials of 28 isolates of Mycoplasma agalactiae obtained from goats in a region (southeastern Spain) where contagious agalactia is endemic. For each isolate, the minimum inhibitory concentration (MIC) against 12 antimicrobials of the quinolone, macrolide, aminoglycoside, and tetracycline families was determined. The antimicrobials with the lowest MIC were enrofloxacin, ciprofloxacin, tylosin, and doxycycline, all with MIC90 (concentration at which growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…Moreover, their MIC 50 and MIC 90 values showed that these antimicrobials are not effective against this pathogen. These results are in agreement with those described in previous studies performed on other mycoplasma species [8, 10, 11, 33]. Hence, our work supports the previously proposed hypothesis about an intrinsic resistance of the mycoplasmas of the M .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, their MIC 50 and MIC 90 values showed that these antimicrobials are not effective against this pathogen. These results are in agreement with those described in previous studies performed on other mycoplasma species [8, 10, 11, 33]. Hence, our work supports the previously proposed hypothesis about an intrinsic resistance of the mycoplasmas of the M .…”
Section: Discussionsupporting
confidence: 94%
“…We evaluated the effect of 18 antimicrobials: spectinomycin (Sigma-Aldrich, USA), kanamycin (Sigma-Aldrich, USA), gentamycin (Sigma-Aldrich, USA), neomycin (Sigma-Aldrich, USA) and streptomycin (Sigma-Aldrich, USA) in a range from 128 μg/ml to 16 μg/ml; ciprofloxacin (Fluka, USA), enrofloxacin (Fluka, USA), marbofloxacin (Tokyo Chemical Industry, Japan), danofloxacin (Fluka, USA), moxifloxacin (Cayman Chemical Company, USA), norfloxacin (Sigma-Aldrich, USA), doxycycline (Sigma-Aldrich, USA), tylosin (Fluka, USA) and tilmicosin (Molekula, UK), which were studied in a range from 12.8 μg/ml to 0.006 μg/ml; and erythromycin (Fluka, USA), spiramycin (Sigma-Aldrich, USA), clindamycin (Cayman Chemical Company, USA) and lincomycin (Sigma-Aldrich, USA), which were evaluated in a range from 12.8 μg/ml to 0.8 μg/ml. The concentration range of these antimicrobials was selected considering data published in previous studies [810]. Different concentrations of antimicrobials were obtained by serial two-fold dilutions from the highest to the lowest concentration.…”
Section: Methodsmentioning
confidence: 99%
“…; Paterna et al . ). Furthermore, half of the isolates had been collected from asymptomatic infections, which suggests that the circulation of these strains with increased MICs within flocks is extensive.…”
Section: Discussionmentioning
confidence: 97%
“…; Paterna et al . ). No data are available as yet concerning the susceptibility of M. agalactiae isolates in France.…”
Section: Introductionmentioning
confidence: 97%
“…have been, however, increasingly documented. Indeed, the ewe and goat field isolates were mostly resistant to erythromycin, indicating that this macrolide would not be a suitable choice for therapy (Antunes et al, 2008;de Garnica et al, 2013c;Paterna et al, 2013). In addition, in a recent published study carried out over the last 25 years in M. agalactiae isolates collected from sheep and goats in France, this species showed increased minimum inhibitory concentrations over time for several antimicrobials used against CA (Poumarat et al, 2016).…”
Section: Mycoplasma Sppmentioning
confidence: 99%